The divine agent in Intertestamental Judaism : the origins of the concept in the Hebrew tradition and its application in the figures of the the "Son of Man" in the Similitudes of Enoch and the "Logos" in the writings of Philo of Alexandria - Taylor, Nicholas Hugh (Department of Religious Studies, 2016)
Bibliography: pages 157-161.